Ocorrência e caracterização de espécies de Cercospora associadas à mancha foliar do milho em Goiás e Paraná - Neves, Danilo Lima das (2012)
Grey leaf spot is one of the most important foliar diseases of maize (Zea mays L.) in Brazil. Previous studies have shown that three Cercospora species can be associated with this disease in the country: C. zeina, C. zeae-maydis and C. sorghi var. maydis; however, still there are limited information about the occurrence of these species in the major maize producing areas, as well as the spatial distribution of these species in maize fields is unknown. The aims of this work were: (i) to identify the Cercospora species occurring in the major maize producing areas of Goiás and Paraná States; (ii) to analyze the spatial distribution of these species in maize fields; (iii) to characterize representative isolates these species based on sequence analyze of ITS-5.8s gene rDNA, and on some phenotypic traits, such as colony morphology and coloration, mycelial growth, morphology of conidia and conidiophores, and pathogenicity. Molecular identification was based on PCR with species-specific primers for C. zeina e C. zeae-maydis. Cercospora sorghi var. maydis was identified based on comparison of their ITS-5.8S rDNA sequences with sequences of Cercospora from GenBank. In the first aim, among the 75 single spore isolates from different areas of Goiás and the 74 isolates from Paraná, C. zeina was the predominant species (90.7 % of isolates) over C. zeae-maydis (9.3 % of isolates) in Goiás, and also predominant (97.3 %) over C. sorghi var. maydis (2.7 % of isolates) in Paraná. The spatial distribution study in one hectare divided in 25 quadrats showed that isolates collected in a field located in Montividiu (n=43) and Rio Verde (n=89) State of Goiás, and isolates from Maringá (n=120), State of Paraná, were C. zeina. The phylogenetic tree inferred with ITS-5.8S rDNA sequences showed that the 16 isolates representatives of C. zeina, the six isolates of C. zeae-maydis and the two isolates of C. sorghi var. maydis formed well-supported groups, with bootstrap support of 84, 89 and 98% to respectively. The comparison of phenotypic traits showed that C. sorghi var. maydis presented higher mycelial growth rate than the others species, and that C. zeina presented lower growth rate then C. zeae-maydis and C. sorghi var. maydis. The distinction between C. zeina and C. zeae-maydis was not conclusive based upon conidia and conidiophores vi morphology. However, these traits allowed to distinguish C. sorghi var. maydis from the other two species. The pathogenicity test, carried out in greenhouse with partial control of temperature and humidity, with plants inoculated at the growth stage V3 by placing colonized sorghum seeds into the whorl of the plants, revealed that only C. zeina and C. zeae-maydis were pathogenic to maize. Significant differences in aggressiveness were found among isolates of the same species and also among isolates of C. zeina and C. zeae-maydis. The aggressiveness average of C. zeae-maydis isolates was significantly higher than the aggressiveness average of C. zeina isolates.